1999
DOI: 10.1034/j.1399-3003.1999.14d28.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atopy on exhaled nitric oxide in patients with stable asthma and rhinitis

Abstract: Influence of atopy on exhaled nitric oxide in patients with stable asthma and rhinitis. Ch. Gratziou, M. Lignos, M. Dassiou, Ch. Roussos. #ERS Journals Ltd 1999. ABSTRACT: The level of exhaled NO is increased in patients with allergic asthma and seasonal rhinitis. The aim of this study was to investigate the significance of atopy on NO production in the lower airways.Measurements of exhaled NO were performed in 131 stable asthmatic patients with chronic mild asthma (95 atopics and 36 nonatopics), 72 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
119
7
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 34 publications
33
119
7
3
Order By: Relevance
“…In contrast with previous findings [16], we observed no significant difference in the eNO level according to the atopic status in the group of asthmatics with rhinitis. However, our results are consistent with those of Berlyne et al [50] comparing eNO to induced sputum, and are in accordance with the hypothesis of a similar physiological process between atopic and non-atopic asthma.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast with previous findings [16], we observed no significant difference in the eNO level according to the atopic status in the group of asthmatics with rhinitis. However, our results are consistent with those of Berlyne et al [50] comparing eNO to induced sputum, and are in accordance with the hypothesis of a similar physiological process between atopic and non-atopic asthma.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are consistent with previous studies, in which eNO levels from two to four times higher than normal were found in atopic asthmatic children [7], teenagers [15] and adults [16]. Among non-asthmatic children, atopic subjects had higher eNO concentrations than non-atopic subjects, which contrasts with previous results showing no difference in eNO levels between atopic and nonatopic individuals either in children [7] or in adults [15,16]. This might be due to the use in these studies of a high (250 mL/s) expiratory flow rate, which has been shown to have poor sensitivity [11,12,17].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations